Whole Elliptical Surface Polishing Using a Doughnut-Shaped MCF Polishing Tool with Variable Tilt Angle - Ming Feng; Yang Lei; Zhixiang Chen; Xianglei Zhang; Xizhang Chen; Youliang Wang (Lubricants, 2022)
Elliptical elements are essential optical surfaces for modifying optical systems. For polishing the whole elliptical surface using doughnut-shaped MCF polishing tool with variable tilt angle, an experimental investigation was conducted in this work. Firstly, a flat workpiece was polished to determine the polishing feasibility. It was found that the middle portion of the polishing tool had optimal ability to remove materials, and the surface roughness Sa at the material removal peak was changed from 134 nm to 17.5 nm within 50 min of polishing. A smoother surface could be obtained using MCF2 slurry and MCF3 slurry, but the use of MCF1 slurry resulted in a rough surface. Then, the effects of working gap h, revolution speed of MCF polishing tool and polishing time on the polishing results were tested to study the polishing characteristics. Sa 9.6 nm and glossiness 278 Gu were obtained, and form error improved from 2.3 μm to 1.3 μm. Finally, the MCF polishing tool was dried to observe the microstructure of the MCF polishing tool after polishing. Abrasive particles were distributed evenly after polishing. It was seen that the abrasive particles were grabbed by the ferric clusters, and the α-celluloses were interleaved between the clusters.